Evaluating Augmented Reality-Supported Project-Based Learning in Digital Economics and Business Education: An Experimental Study - Dede Rusmana; Fuad Abdul Fattah; Wening Patmi Rahayu; Rachmad Hidayat (South Sulawesi Education Development (SSED), 2025)
Integrating Augmented Reality (AR) into Project-Based Learning (PjBL) was evaluated for its effect on undergraduates’ critical thinking in a Digital Economics and Business course. A quasi-experimental design compared a control class (n = 40) and an AR-supported class (n = 34) over 16 meetings using the same syllabus; the experimental class used Assemblr Edu during project work. Critical thinking was measured with a 5-item test (0–100) administered pre and post-intervention and scored by external raters. Because Shapiro–Wilk tests indicated non-normality (all p < 0,05), Mann–Whitney U and Friedman tests were applied (α = 0,05). Baseline equivalence held (pretest U = 655,0 and Z = −0,276, p= 0,782). After the intervention, the between-group difference remained non-significant (U = 624,5 and Z = −0,612, p = 0,540). Within-group gains were significant for both classes: control χ²(1)= 24,641, p< 0,001 (mean ranks pre 1,11 to post 1,89); experimental χ²(1)=12,500, p< 0,001 (pre 1,21 to post 1,79). In short, PjBL improved critical thinking regardless of AR, and AR did not add a detectable short-term advantage. In this context, implementation should prioritize problem task alignment and sustained practice over technology adoption.